2016
DOI: 10.3390/min6030074
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Minerals and Elements in the Late Permian Coal Seams of the Shiping Mine, Sichuan, Southwestern China

Abstract: Volcanic layers in coal seams in southwestern China coalfields have received much attention given their significance in coal geology studies and their potential economic value. In this study, the mineralogical and geochemical compositions of C19 and C25 coal seams were examined, and the following findings were obtained. (1) Clay minerals in sample C19-r are argillized, and sedimentary layering is not observed. The acicular idiomorphic crystals of apatite and the phenocrysts of Ti-augite coexisting with magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The Southern area had the highest value, with a particularly high arithmetic average reaching to 1.21 µg/g, nearly five times as high as the value reported by Dai et al [7]. The coalfields (mines) with abnormally high concentrations of cadmium in coal, such as the Moxinpo Coalfield in Chongqing (31.19 µg/g) [11], the Chenxi Mine in Hunan (5.01 µg/g) [10], the Shiping Mine in Sichuan (5.91 µg/g) [84], are located in this coal-distribution area. In the other coal-distribution areas, cadmium concentrations were all lower than that estimated by Dai et al [7].…”
Section: Distribution Characteristics Of Cadmium In Chinese Coals In mentioning
confidence: 93%
“…The Southern area had the highest value, with a particularly high arithmetic average reaching to 1.21 µg/g, nearly five times as high as the value reported by Dai et al [7]. The coalfields (mines) with abnormally high concentrations of cadmium in coal, such as the Moxinpo Coalfield in Chongqing (31.19 µg/g) [11], the Chenxi Mine in Hunan (5.01 µg/g) [10], the Shiping Mine in Sichuan (5.91 µg/g) [84], are located in this coal-distribution area. In the other coal-distribution areas, cadmium concentrations were all lower than that estimated by Dai et al [7].…”
Section: Distribution Characteristics Of Cadmium In Chinese Coals In mentioning
confidence: 93%
“…Significant uranium enrichment in coals only occurs in Shanxi, Yunnan, Guizhou, Guangxi, Xinjiang, Inner Mongolia, Sichuan, and Chongqing Provinces of China (Table 1), e.g., the Datong coal (averaging 38.2 mg/kg and 28.8 mg/kg uranium [31]), the Dazhai coal (52.5 mg/kg [32] and 56.0 mg/kg [33]), the Yanshan coal (167 mg/kg [34] and 153 mg/kg [35]), the Luquan coals (34.1 mg/kg [36]), the Guiding coal (229 mg/kg [34] and 200 mg/kg [30]), the Puan coal (32.4 mg/kg [37]), the Zhijin coal (49.6 mg/kg [38]), the Heshan coal (10.2 mg/kg to 326 mg/kg [39][40][41][42]), the Yishan coal (71.7 mg/kg [43]), the Sawabuqi coal (365 mg/kg [44]), the Yili coal (320 mg/kg [45] and 147 mg/kg [46]), the Shenli coal (25.9 mg/kg [47]), the Shiping coal (39.8 mg/kg [48]), and the Moxinpo coal (376 mg/kg [49]). …”
Section: Significant Enrichment Of Uranium In Some Chinese Coalsmentioning
confidence: 99%
“…It is suggested that the dominant terrigenous material of the Lopingian coals in southwestern China is the basaltic Kangdian Upland, which is typically enriched in Sc, V, Cr, Co, Ni, Cu and Zn [10,45,64,[68][69][70][71]. For example, the dominant terrigenous material for the coals in the Xinde Mine, Yunnan Province, southwestern China is identified as the Kangdian Upland, with high concentrations of Sc, V, Cr, Co, Ni, Cu and Zn in the coals [45].…”
Section: Sediment Source Regionmentioning
confidence: 99%